Emotional eating patterns in a sample of Mexican adolescents - De Gracia, Manuel; Trujano, Patricia; Nava, Carlos; Jiménez, Nuria (International Journal Of Community Medicine And Public Health, 2024)
Background: Eating patterns can be used to regulate emotions. Recent research has focused on emotional eating, aiming to determine the leading psychological causes of emotional eating based on the habits of a group of Mexican adolescent scholars that are between 15-17 years old (n=417). Methods: Five mechanisms measured emotional aspects and eating patterns; they were analyzed with different statistical tools. Results: There weren’t significant gender differences in the feelings of emotional restlessness between boys and girls, nor the expected feelings of anxiety, anger, frustration, and depression. There weren’t variations in the types of emotional eating between the normal weight (average weight) and overweight groups. Nevertheless, there was a significant relationship between emotional eating (negative feelings) and bulimic eating patterns, showing more dependency on eating after receiving stimuli related to eating, regardless of satiety and hunger. Negative moods and emotions appeared as a result of parents trying to have more control over eating. When having obesity, there was less oral intake control, which led to the risk of overweight/obesity. Finally, less parental control over eating slightly increased the risk of overweight/obesity. However, the most risk is associated to diet restrictions and worry about food caused by fear to be overweight. Conclusions: Obesity in children and teenagers is a public health problem. Its prevention must be a priority; therefore, knowing and working on its risk factors is urgent.